(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of the research is to measure the relationship and effect of the application of total production maintenance TPM in the operational strategy, as it is considered one of the most important strategies for the process of restoring production losses because of inefficient equipment. Competitive edge in the global market by upgrading the operational strategies of OS in the application of TPM in those institutions that apply both H-OS-oriented and P-OS-oriented strategies where the strategy has been identified as a critical success factor. The aim of this study is to attempt to consider the application of comprehensive productive maintenance in industrial establishments